Poverty Reduction Strategy in Bangladesh : Rethinking participation in policy making - Kamruzzaman, Palash (Book collections on Project MUSE., 2014)
This book analyses government relationships with International Financial Institutions (IFIs) to evaluate the role of citizen participation in formulating national poverty reduction policies in low income countries.